CLINICAL EFFECTIVENESS OF TITANIUM CAD/CAM RETAINERS FROM A BIOCHEMICAL POINT OF VIEW - Vladimir Petrunov (Peytchinski Publishing, 2023)
Following the integration of fixed retainers into the clinical practice, an increasing number of orthodontists prefer this retention method. Further to the proven advantages of those retainers, however, there are some deficiencies, which, if not taken into consideration, might compromise the good treatment result. CAD-CAM methods employ a different approach in design, materials and method of fabrication, and clinical procedures with respect to fixation. This allows for the avoidance of a large part of the deficiencies of the fixed retainers that are made manually. Aim: Our aim is to demonstrate the clinical effectiveness of titanium CAD/CAM fixed retainers. Materials and methods: Swing (DOF) Laboratory scanner was used to scan the models. Retainers were designed through Exocad Matera (Exocad GmbH) software. Retainers were fabricated of titanium Ti G5 (SILADENT Dr Böhme & Schöps GmbH) discs, machined with CORiTEC 650i (Imes-icore GmbH) 5-axis dental milling machine. Results: The outcome is a retainer, which is excellently fitting to the dental surface, absolutely passive, resistant to plastic deformation, fracture-proof and with an extremely easy clinical fixing procedure. Conclusion: CAD/CAM methods employ an innovative approach, providing a different manufacturing technology and the use of various materials for the purposes of fixed retention. These methods eliminate a significant part of the deficiencies of the conventional manually bent retainers.